2013
DOI: 10.1111/exd.12276
|View full text |Cite
|
Sign up to set email alerts
|

Impact of next generation sequencing on diagnostics in a genetic skin disease clinic

Abstract: Individuals with inherited skin diseases often pose one of the most difficult diagnostic challenges in dermatology. The hunt for the underlying molecular pathology may involve candidate gene screening or linkage analysis, which is usually determined by the initial history, the physical findings and laboratory tests. Recent technical advances in DNA sequencing, however, are shifting the diagnostic paradigm. Notably, next-generation sequencing allows a more comprehensive approach to diagnosing inherited diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 43 publications
2
50
0
2
Order By: Relevance
“…Next‐generation sequencing (NGS) technologies applying whole‐exome sequencing (WES) enables sequencing all protein‐coding DNA regions in one run. Preliminary reports indicate a high diagnostic yield applying NGS in the molecular investigation of various genodermatoses in the clinic . In 2013, Oslo University Hospital implemented WES with analysis of ichthyosis‐related genes as a routine diagnostic test for patients suffering from inherited ichthyosis.…”
Section: Introductionmentioning
confidence: 99%
“…Next‐generation sequencing (NGS) technologies applying whole‐exome sequencing (WES) enables sequencing all protein‐coding DNA regions in one run. Preliminary reports indicate a high diagnostic yield applying NGS in the molecular investigation of various genodermatoses in the clinic . In 2013, Oslo University Hospital implemented WES with analysis of ichthyosis‐related genes as a routine diagnostic test for patients suffering from inherited ichthyosis.…”
Section: Introductionmentioning
confidence: 99%
“…It can be performed on the entire genome, which includes noncoding areas of the DNA (introns), coding areas of the DNA (exons) and mitochondrial DNA, or limited to coding areas of the genome. The former is referred to as whole‐genome sequencing (WGS), whereas the latter is referred to as whole‐exome sequencing (WES) . The exome involves roughly 1.5% of the human genome, encompassing most exons of about 20,000 human genes; WES is therefore less labour‐intensive than WGS .…”
Section: Next‐generation Sequencing (Ngs)mentioning
confidence: 99%
“…Takeichi et al [46] have recently demonstrated the impact of next-generation sequencing technologies on clinical genetics in the dermatology field. Indeed, next-generation sequencing can reveal two autosomal recessive disorders in a single family.…”
Section: Lipnmentioning
confidence: 99%